Raman lidar-derived optical and microphysical properties of ice crystals within thin Arctic clouds during PARCS campaign - P. Chazette; J.-C. Raut (Atmospheric Measurement Techniques, 2023)
Cloud observations in the Arctic are still rare, which requires innovative observation techniques to assess ice crystal properties. We present an original approach using the Raman lidar measurements applied to a case study in northern Scandinavia. The vertical profiles of the optical properties, the effective radius of ice crystals and ice water content (IWC) in Arctic semi-transparent clouds were assessed using quantitative ground-based lidar measurements at 355 nm performed from 13 to 26 May 2016 in Hammerfest (north of Norway, 70 ∘ 39 ′ 48 ′′ N, 23 ∘ 41 ′ 00 ′′ E). The field campaign was part of the Pollution in the ARCtic System (PARCS) project of the French Arctic Initiative. The presence of low-level semi-transparent clouds was noted on 16 and 17 May. The cloud base was located just above the atmospheric boundary layer where the 0 ∘ C isotherm reached around 800 m above the mean sea level (a.m.s.l.). To ensure the best penetration of the laser beam into the cloud, we selected case studies with cloud optical thickness (COT) lower than 2 and out of supercooled liquid pockets. Lidar-derived multiple scattering coefficients were found to be close to 1 and ice crystal depolarization around 10 %, suggesting that ice crystals were small and had a rather spherical shape. Using Mie computations, we determine effective radii between ∼7 and 25 µm in the clouds for ice water contents between 1 and 8 mg m −3 , respectively. The uncertainties regarding the effective radii and ice water content are on average 2 µm and 0.65 mg m −3 , respectively.